Non-Dose-Dependent Changes in Liver Enzyme Levels of Children With Epilepsy on Treatment With Sodium Valproate - Aduragbenro Deborah A. Adedapo; Winifred Eseoghene Demaki; IkeOluwa Lagunju (SAGE Publishing, 2020)
Background: Sodium valproate (VPA) is considered as the drug of choice for the treatment of generalized epilepsy in children. Sodium Valproate may be hepatotoxic. Aim: To assess the level of derangement of liver enzymes in children with epilepsy on treatment with sodium valproate. Methods: A cohort study. One hundred fifty-three children, comprising 51 with epilepsy on treatment with VPA (group I), 51 with epilepsy on treatment with other antiepileptic drugs (AEDs) but not VPA (group II), and 51 with nonconvulsive disorders (group III) had liver function tests performed for them. Data were analyzed by SPSS version 23.0. Results: There were 85 males and 68 females, aged 6 months to 14 years (median = 7.0 years). There was no significant difference in the mean plasma levels of alanine transaminase (ALT), alkaline phosphatase, and gamma glutamyl transferase across the three groups of children. The mean aspartate transaminase level was significantly higher in children in group III. There was a statistically significant negative correlation between the duration of AED therapy and the mean serum level of AST ( r = −0.266, P = 0.016). The serum ALT level showed a statistically significant positive correlation with the duration of AED therapy ( r = 0.268, P = 0.015). Conclusion: Sodium valproate monotherapy does not appear to be associated with significant hepatotoxicity in children in our cohort.